Efektivitas Penambahan Karbon Aktif Cangkang Kelapa Sawit (Elaeis Guineensis) dalam Proses Filtrasi Air Sumur - Muhammad Fadhillah; Denay Wahyuni (Jurnal Kesehatan Komunitas, 2016)
The impact of water pollution can cause an imbalance of the ecosystem and a contagious disease. So,it is necessary to refine the water before it is used to improve water quality. One that can be used to purify water is palm shell activaited charcoal (Elaeisguineensis). The purpose of this study is to determine the effectiveness of the addition of activated charcoal palm shells in the filtration process of the physical characteristics (turbidity, Ph, smell and taste) of the well. This research is an experiment using a completely randomized design (CRD). Well water filtration is performed with 4 treatments and 3 repetitions namely: 1). without passing through the sand filter (control), 2).through the sand filter without palm shell activaited charcoal, 3). through the filter sand with the addition of palm shell activaited charcoalwith a thickness of 10 cm, and 4). thickness of 15 cm. One way ANOVA was used for data analysis. The turbidityanalysis is 100.0; 50.5; 40.4; and 47.5 respectively for the control, without activated charcoal, 10 cm and 15 cm with activated charcoal. The result showed that there is no significant differences the turbidity of the contratedwater with the turbidity of other treatments. water pH <7 becomes 8.99. Analysis found the smell and taste of water through the filtration process with the addition of activated charcoal to eliminate odor and taste in the water. The addition of palm shell activaited charcoal with a thickness of 10 cm is quite effective in well water filtration process and can improve the physical quality of the water.